2015
DOI: 10.1002/elan.201500037
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single Layer and Bilayer Biosensors Based on Crosslinking of Penicillinase for Potentiometric Detection of Penicillin in Milk and Antibiotics

Abstract: The use of bilayers for fabrication of biosensors is advantageous for increasing enzyme loading. Substantial improvement in sensitivity is often achieved through immobilisation of the enzyme in both layers. In particular, the use of cross linking agents such as glutaraldehyde (GLA), bovine serum albumin (BSA) and polyvinyl alcohol (PVA) are beneficial for enhancing enzyme stability and, hence, for fabricating stable biosensors. The successful fabrication of a single layer BSA‐GLA‐P’nase biosensor for potentiom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Despite the low concentrations detectable by the sensor, the authors concluded that their device was more amenable for the detection of the analyte at higher concentrations (from 10 ppm to 20 ppm). One year later, the same authors published another paper 33 reporting the detection of penicillin and other antibiotics in the context of a potentiometric sensor. In this new report, the research compared a single layer and a bilayer biosensor, both containing penicillinase enzyme as a bioreceptor.…”
Section: Amperometric Methodmentioning
confidence: 99%
“…Despite the low concentrations detectable by the sensor, the authors concluded that their device was more amenable for the detection of the analyte at higher concentrations (from 10 ppm to 20 ppm). One year later, the same authors published another paper 33 reporting the detection of penicillin and other antibiotics in the context of a potentiometric sensor. In this new report, the research compared a single layer and a bilayer biosensor, both containing penicillinase enzyme as a bioreceptor.…”
Section: Amperometric Methodmentioning
confidence: 99%
“…There are various biocatalytic components, including whole cells, enzymes or multi-enzyme systems, organelles in cells, or tissues in plants or animals. Signals are obtained by measuring the products generated by catalyzed chemical reactions between enzymes and substrates 91 . The affinity bioreceptor generates an analyte-receptor complex through the interaction of the recognition element and analyte, which can be detected by labeling (fluorescent or enzymatic) or observing the transducer's physical-chemical properties .…”
Section: Antibiotic Quantification With Nanobiosensorsmentioning
confidence: 99%
“…Produkt lub produkty uboczne enzymów mogą być elektroaktywne, co oznacza, że ich aktywność można śledzić za pomocą amperometrii. Obecnie opracowano szereg biosensorów enzymatycznych opartych na sieciowaniu albuminą surowicy wołowej (BSA) [10], służących do wykrywania związków toksycznych. Enzym Acetylocholinesteraza (AChE) ma bardzo wysoką aktywność katalityczną oraz istnieje szeroka gama związków toksycznych, które hamują ten enzym, dlatego też AChE jest często wykorzystywany do tworzenia biosensorów opartych na analizie inhibicji.…”
Section: Wstępunclassified